2008
DOI: 10.1097/nmd.0b013e3181775a4e
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of the DSM-IV Obsessive-Compulsive Personality Disorder Construct as a Prototype Category

Abstract: The study evaluated the quality of the DSM-IV obsessive-compulsive personality disorder (OCPD) construct as a prototype category. A sample of 2237 patients from the Norwegian Network of Psychotherapeutic Day Hospitals was examined by a variety of psychometric analyses. A high number of OCPD patients (77%) had co-occurrent PDs, but only the co-occurrence with paranoid was significantly higher than expected. Exploratory factor analysis of the PD criteria indicated that OCPD consists of 2 dimensions. The first di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
62
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 57 publications
12
62
0
1
Order By: Relevance
“…Nearly all etiologies of obsessive character are psychoanalytic or psychosocial in nature; consequently, nearly all etiologies are untenable. Even in the vanishingly rare instances in which obsessive biology is considered (Millon and Davis 1996;Hummelen et al 2008), psychoanalytic language is used and psychoanalytic assumptions are conserved (Hertler 2014b). …”
mentioning
confidence: 99%
“…Nearly all etiologies of obsessive character are psychoanalytic or psychosocial in nature; consequently, nearly all etiologies are untenable. Even in the vanishingly rare instances in which obsessive biology is considered (Millon and Davis 1996;Hummelen et al 2008), psychoanalytic language is used and psychoanalytic assumptions are conserved (Hertler 2014b). …”
mentioning
confidence: 99%
“…[54][55][56] Also, it has been suggested that deleting hoarding and miserliness items from the set of OCPD criteria may improve the validity of the OCPD diagnosis. 57,58 Similarly, in longitudinal studies, only non-hoarding OCPD criteria, such as preoccupation with details, rigidity and stubbornness, and reluctance to delegate, were predictive of the diagnosis of OCPD two years later. 59 Therefore, most studies suggest that the association between hoarding and OCPD is due to overlapping item content, i.e., because hoarding was assumed to be one of the eight criteria of OCPD.…”
Section: Is Hoarding Different From Ocd and Ocpd?mentioning
confidence: 99%
“…43 A study in a different cohort considered miserliness and hoarding to be unsatisfactory for the diagnosis. 44 Notwithstanding the above, the DSM-5 retained all eight DSM-IV criteria. Compulsive hoarding was recognized as a separate disorder, classified within the OCRD category.…”
Section: Dsmmentioning
confidence: 99%
“…67 Studies that have examined the internal consistency and factor structure within OCPD have suggested that the hoarding and miserliness criteria might be less indicative of OCPD, and that the OCPD construct may be improved with their exclusion. 42,44 Three studies that recruited large samples of individuals with compulsive hoarding [68][69][70] noted the lack of any specific relationship between hoarding and OCPD and considered that the link could largely be explained by overlapping item content. On the other hand, other studies have shown that patients with OCD and comorbid OCPD are characterized by an increased frequency of hoarding symptoms compared to noncomorbid OCD.…”
Section: Phenomenologymentioning
confidence: 99%